Memegang Hewan Rentan dan Menangani Produknya Berisiko Besar Tertular Antraks Kulit di Daerah Endemis - Basri, Chaerul; Maria Kiptiyah, Nuning (Jurnal Veteriner; Vol 11 No 4 (2010), 2010)
The objectives of this study were to identify risk factors associated with historical of animals contact and animalproducts on the incident of cutaneous anthrax in humans in Bogor District. The research designed used in this study CaseControl of Observational Epidemiology. Patients of cutaneous anthrax disease record in Puskesmas (Center for HealthServices) were used as a case. Inhabitants in Bogor district living in the same area with patients of cutaneous anthrax andnot showing clinical signs of cutaneous anthrax. The data were collected by structured interviews and direct observations.Data analysis was carried out in three steps, consisting univariate for analysis of frequency distribution, bivariate withChi-square and also multivariate analysis for prediction model of logistic regression. All analysis processed by SPSS 13.0.It can be concluded that the first risk factor associated with the occurrence of cutaneus anthrax was holding susceptibleanimals with Odds Ratio (OR) of 6.648 (95% Confidence Interval (CI) = 2,914-15,167), the second risk factor was meathandling with OR of 5.318 (95% CI: 1,801-15,702). It showed that for people who live in endemic area of anthrax, holdingsusceptible animals sixth times more likely get cutaneous anthrax.
Keywords: cutaneous anthrax, contact, susceptible animal, odds ratio